The significance and timing of sheetflood vs braided channel deposition on lacustrine fan deltas, Junggar Basin, NW China. Issue 7 (3rd October 2017) - Peng, B.; Jin, Z.; Wang, J.; Chang, T.; Zhu, X.; Gul, B.
ABSTRACT: The fan-delta reservoir play has become an important exploration target within the Junggar Basin, especially in the Mabei area within the Mahu Sag, where a fan-delta oil and gas pool has been recently discovered. The sedimentary characteristics, distribution patterns and formation mechanisms of the fan-delta clastic bodies in Lower Triassic Baikouquan Formation (T1b) were studied using seismic, well log and core data accompanied by a flume tank experiment and a modern analogue depositional study. The T1b in the Mabei area is composed of a fan delta consisting of fan-delta plain (including debris flow deposits, sheetflood deposits, braided channel deposits, and floodplain deposits), fan-delta front (including subaqueous reworked sheetflood deposits and distal sheetflood deposits) and muddy lake deposits. The sheetflood deposits, characterised by moderately sorted conglomerates with brown matrix, form during the peak flooding. They are widespread and sheet-like, occupying the major portion of the fan-delta plain. The braided channel deposits are characterised by well-sorted and clast-supported conglomerates and pebbly sandstones, formed later during the falling flow stage. Owing to the decline in volume and velocity, and the formation of continuously braided fluid flow, the sediments of the flood period are reworked, generating the braided channels. Laterally, the braided channels occur as belts of clastic bodies surrounded by continuous sheetflood deposits. Vertically, the braided channels are interbedded between the sheetflood deposits. The subaqueous reworked sheetflood deposits are characterised by greyish-green, well-sorted and clast-supported conglomerates, whereas the distal sheetflood deposits are characterised by well-sorted sandstones, intercalated with mudstone. The subaqueous reworked sheetflood and distal sheetflood deposits are a distal partly subaqueous extension of the main sheetflood deposits, albeit reworked by basinal currents and waves. The distal sheetflood deposits form on distal fringes of the sheetfloods and are more thoroughly reworked by longshore and wave currents. The braided channel, subaqueous reworked sheetflood and distal sheetflood deposits can form high-porosity reservoirs. These findings challenge the common view and suggest that the channelised facies on the fans are not the main flood events; rather, the more extensive sheetfloods are the major flood events.